Determining the behaviours required to develop the capacity to change for Malaysia's workforce / Yam Wei Mun - Yam, Wei Mun (2012)
This research surveyed the supportive and non-supportive behaviour factors, which influenced the change capacity of an organisation for the Malaysia workforce. Survey tools were adopted from two (2) previous researches - Judge and Douglas (2009) and Szamosi and Duxburry (2002) are synthesized to establish a new assessment tool for organisation whom wish to embark on any Change / Transformation activities. These tools assessed the influence of the Supportive and Non-Supportive Behaviours on Organisational Support, Employee/Organisational Commitment and Change Leadership and Sponsorship. The survey output was based on 121 respondents of varying demographics – years of service, industry and functional area, given the unit of analysis is at the organisation level. The responses were gathered through online and offline (hardcopy). The latter was opted to increase the level of responses. The results of the research depicted that the supportive behaviour factors have higher influence over the non-supportive behaviour factors, which provide an indication that the workforce in Malaysia is optimistic and able to support changes in their organisation, if need be. However, the non-supportive behaviour plays a key role in influencing the Organisational Support where failure to align everyone in an organisation (Top, Mid and Lower Management) will have a detrimental effect on any Transformation Programme. Unlike for Employee/Organisational Commitment and Change Leadership and Sponsorship, the supportive behaviour factors have higher influence as compared to the non-supportive behaviour. The findings from this research provide the Organisational Development (OD) practitioner to assess the readiness of their organisation to allow them to plan the proper intervention which supports any transformation and change initiatives. As to ensure that the Organisation Support aspect is properly managed, additional research using the Geert Hofstede cultural dimension, especially in the Asian context – multicultural. Besides that, it is also recommended that additional research can be considered in determining if leadership styles (Burns, 1978) will moderate the existing theoretical framework.